2020
DOI: 10.1186/s40246-020-00280-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of the human host influencing the coronavirus-associated phenotypes (SARS, MERS and COVID-19): rapid systematic review and field synopsis

Abstract: The COVID-19 pandemic has strengthened the interest in the biological mechanisms underlying the complex interplay between infectious agents and the human host. The spectrum of phenotypes associated with the SARS-CoV-2 infection, ranging from the absence of symptoms to severe systemic complications, raised the question as to what extent the variable response to coronaviruses (CoVs) is influenced by the variability of the hosts’ genetic background. To explore the current knowledge about this question, we designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 97 publications
3
75
1
2
Order By: Relevance
“…The only other supportive evidence for a role in disease pathophysiology, in studies included here, came from a single transcriptomic study for each; there was no evidence from protein–protein interaction, proteomics or genetics 51 , 58 . Candidate gene association studies are highly dependent on prevalence of functional variants and, while overlapping to a limited extent with results of large-scale screens included here, have been notably unable to detect significant associations with ACE2 18 . Integrating perturbation data will thus add considerably to our ability to interpret the relative importance of these factors.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The only other supportive evidence for a role in disease pathophysiology, in studies included here, came from a single transcriptomic study for each; there was no evidence from protein–protein interaction, proteomics or genetics 51 , 58 . Candidate gene association studies are highly dependent on prevalence of functional variants and, while overlapping to a limited extent with results of large-scale screens included here, have been notably unable to detect significant associations with ACE2 18 . Integrating perturbation data will thus add considerably to our ability to interpret the relative importance of these factors.…”
Section: Discussionmentioning
confidence: 84%
“…Finally, we also performed a comparison of our output with a recently published systematic review also identifying genes implicated in betacoronavirus infection and focused on peer-reviewed articles concerned with biomarkers associated with a clinical diagnosis of SARS or associated syndromes 18 . This review identified 22 unique genes, 6 of which overlap with the MAIC output and are detailed in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…So far, there was no rationale to consider TPCN2 among candidate genes associated to the phenotype variability of COVID-19. A recent systematic review did not detect any study investigating TPCN2 as candidate gene associated with CoVs infection and outcomes [ 4 ]. A large genome-wide association study (GWAS) investigated the genomic variants associated with COVID-19.…”
mentioning
confidence: 99%
“…A notable effort was made to analyze 12 autosomal loci ( STAT1 on chromosome 2, TLR 3 on chromosome 4, IRF7 and UNC93B1 on chromosome 11, TBK1 and STAT2 on chromosome 12, IRF9 and TRAF3 on chromosome 14, TICAM1/TRIF and IRF3 on chromosome 19, IFNAR1 and IFNAR2 on chromosome 21) and one X linked locus (NF-κB essential modulator— NEMO/IKBKG ) in COVID-19 patients with life-threatening pneumonia vs. mild and asymptomatic COVID-19 cases (control group) [ 113 , 114 ]. The studied loci were connected to viral encephalitis, complications after measles, mumps, and rubella (MMR) vaccination and ARDS/critical influenza pneumonia [ 113 , 115 , 116 ]. As regards the 12 autosomal loci, a significant enrichment in what are predicted to be loss-of-function (pLOF) variants in patients vs. controls was detected under an autosomal-dominant (AD) mode of inheritance ( Table 3 ).…”
Section: Other Immune Response Genesmentioning
confidence: 99%